DAMPAK PROGRAM BANK SAMPAH TERHADAP EKONOMI MASYARAKAT (Studi Pada Bank Sampah Desa Nijang Kecamatan Unter Iwes) - Ishak Rahman; Roos Nana Sucihati; Sonia Gina Risqullah (Jurnal Ekonomi & Bisnis, 2021)
The purpose of this study was to know the impact of waste bank program toward the communities’ economy before and after the waste bank program. The type of this study was comparative study which used descriptive qualitative methods. The data used in this study was primary data. The tool used to collect data was questionnaire.The number of samples in this study were 49.The technique used to analyzed data was the average difference test using SPSS version 16.00. Based on the data analysis, it was concluded that there was positive impact toward economic income of communities in Nijang Village after the existence of Waste Bank program.Based on the results of the Paired Sample T-Test, it was shown by the decision making, it was known that the significance value (2 tailed) was 0.000 <0.05, with the average difference test results before the waste bank program of Rp.27,875 and after Rp.2,694,532 then we can conclude that there was a significant difference between customer income before and after the Waste Bank program.